Extending the Technology Acceptance Model: Contextualizing Trust and Usability in Shaping Online Consumer Behavior in Dhaka, Bangladesh - Afrin, Rumana; Sarker, Sahin Akter (CV. Literasi Indonesia, 2025)
With the rapid growth of e-commerce in the Asian region, understanding the drivers of online purchasing decisions is crucial for businesses and policymakers. Hence, this study extends the Technology Acceptance Model (TAM) to examine key factors shaping online consumer behavior in Dhaka, Bangladesh, an emerging e-commerce market marked by low trust and infrastructural limitations. Building on TAM’s core constructs, ‘perceived usefulness’ and ‘perceived ease of use’, researchers incorporate trust/security and delivery reliability as critical contextual variables. Data from 200 respondents reveal that price discounts and website usability significantly influence purchase intentions, followed by delivery time and customer reviews. Regression and ANOVA analyses confirm these variables’ predictive power. Trust and security concerns emerge as major antecedents to perceived usefulness, reflecting the unique challenges of digital adoption in Dhaka. The findings validate TAM’s relevance while demonstrating the need for its contextual adaptation in emerging markets. Young, tech-savvy consumers dominate the online shopping landscape, suggesting that targeted design and trust-building initiatives are essential. This research offers strategic insights for e-commerce platforms and policymakers aiming to optimize consumer engagement and satisfaction in Bangladesh’s rapidly evolving digital economy.